The Meaning of Circular Determinism in the Context of the Synergetic Aspect of the World - Hovhannisyan, Lilit (Bulletin of Yerevan University E: Philosophy, Psychology, 2014)
This article analyzes the conception of circular determinism which has been suggested at the end of 20th century. Besides that, the differences of straightline determinism and circular determinism (the latter contains correspondence determinism, indeterminism and probable determinism) are also examined in this article. If, by means of the straightline determinism, cannot be explained why the concrete element “cooperates” with the other concrete element but not with any element, then by means of circular determinism synergy can explain the reasons of "cooperation" of elements. The place and meaning of circular determinism in the context of the synergetic aspect of the world are also examined in the article.
Keywords: scientific picture of the world, straight-line determinism, determinism of vicious circle, circular determinism, synergy, causative circles